2019
DOI: 10.1016/j.pdpdt.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Methyl aminolevulinate-based photodynamic therapy of Bowen´s disease: Observational study of 21 lesions

Abstract: Background: Although surgical removal is the treatment of choice in Bowen's disease (BD), there are cases in which by age, comorbidities, use of anticoagulants, location, cosmetic result, or size, it is preferable to use other alternative treatments such as cryotherapy, 5-fluorouracil cream, imiquimod 5% cream or photodynamic therapy (PDT). Efficacy of PDT in BD is supported by substantial research and clinical data. Objectives: This study aimed to evaluate the long term effectiveness of methyl aminolevulinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…Furthermore, in the study comparing ACL-PDT and AFL-PDT, AFL-PDT was considered less painful, but the reason remained unknown [23]. Finally, as we discussed above, all treatment-related AEs were moderate or mild, and the durations were short, ranging from days to weeks [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the study comparing ACL-PDT and AFL-PDT, AFL-PDT was considered less painful, but the reason remained unknown [23]. Finally, as we discussed above, all treatment-related AEs were moderate or mild, and the durations were short, ranging from days to weeks [4].…”
Section: Discussionmentioning
confidence: 99%
“…The lesions usually appear as slow-growing, scaly, reddish patches or plaques with well-defined irregular edges [3]. Although the disease is not life-threatening, there is still a 3–5% risk of BD lesions developing into invasive SCC [4, 5]. In addition, one-third of the invasive SCCs developed from BD may metastasize [6].…”
Section: Introductionmentioning
confidence: 99%
“…Также имеется сообщение об успешном применении геля, содержащего ингенол мебутат, для лечения очагов болезни Боуэна небольших размеров [46]. Фотодинамическая терапия являе тся хорошо зарекомендовавшим себя терапевтическим вариантом при актинических кератозах, базальноклеточном раке (узловой вариант) и при лечении болезни Боуэна [47][48][49][50]. Данная терапия основана на сочетании света и светочувствительных веществ (порфиринов) в присутствии кислорода, молекулам которого передается энергия фотонов, поглощенная порфиринами [51].…”
Section: обзор литературыunclassified
“…Several randomized control trials have also demonstrated superiority of combined MAL-PDT to cryotherapy and ALA-PDT to topical 5-FU, but these results are inconsistent and long-term clearance rates are similar. 14,39 Multiple case reports have demonstrated long-term success of peri-and subungual SCCis treated with PDT. Each of the documented subungual cases included at least partial nail plate avulsion, all of which re-grew.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Several randomized control trials have also demonstrated superiority of combined MAL-PDT to cryotherapy and ALA-PDT to topical 5-FU, but these results are inconsistent and long-term clearance rates are similar. 14,39…”
Section: Sccis Treatment Optionsmentioning
confidence: 99%